Predicted benefit of an implantable cardioverter-defibrillator: the MADIT-ICD benefit score. (8th January 2021) - Younis, Arwa; Goldberger, Jeffrey J; Kutyifa, Valentina; Zareba, Wojciech; Polonsky, Bronislava; Klein, Helmut; Aktas, Mehmet K; Huang, David; Daubert, James; Estes, Mark; Cannom, David; McNitt, Scott; et al.
Abstract: Aims: The benefit of prophylactic implantable cardioverter-defibrillator (ICD) is not uniform due to differences in the risk of life-threatening ventricular tachycardia (VT)/ventricular fibrillation (VF) and non-arrhythmic mortality. We aimed to develop an ICD benefit prediction score that integrates the competing risks. Methods and results: The study population comprised all 4531 patients enrolled in the MADIT trials. Best-subsets Fine and Gray regression analysis was used to develop prognostic models for VT (≥200 b.p.m.)/VF vs. non-arrhythmic mortality (defined as death without prior sustained VT/VF). Eight predictors of VT/VF (male, age < 75 years, prior non-sustained VT, heart rate > 75 b.p.m., systolic blood pressure < 140 mmHg, ejection fraction ≤ 25%, myocardial infarction, and atrialarrhythmia) and 7 predictors of non-arrhythmic mortality (age ≥ 75 years, diabetes mellitus, body mass index < 23 kg/m 2, ejection fraction ≤ 25%, New York Heart Association ≥II, ICD vs. cardiac resynchronization therapy with defibrillator, and atrial arrhythmia) were identified. The two scores were combined to create three MADIT-ICD benefit groups. In the highest benefit group, the 3-year predicted risk of VT/VF was three-fold higher than the risk of non-arrhythmic mortality (20% vs. 7%, P < 0.001). In the intermediate benefit group, the difference in the corresponding predicted risks was attenuated (15% vs. 9%, P < 0.01). In the lowest benefit group, the 3-year predicted risk of VT/VF was similar to the risk of non-arrhythmic mortality (11% vs. 12%, P = 0.41). A personalized ICD benefit score was developed based on the distribution of the two competing risks scores in the study population (https://is.gd/madit ). Internal and external validation confirmed model stability. Conclusions: We propose the novel MADIT-ICD benefit score that predicts the likelihood of prophylactic ICD benefit through personalized assessment of the risk of VT/VF weighed against the risk of non-arrhythmic mortality. Graphical Abstract: